2022
DOI: 10.1021/acs.jmedchem.2c01243
|View full text |Cite
|
Sign up to set email alerts
|

Making Protein Degradation Visible: Discovery of Theranostic PROTACs for Detecting and Degrading NAMPT

Abstract: Proteolysis-targeting chimera (PROTAC) is emerging as a promising technology in targeted protein degradation and drug discovery. However, there is still a lack of effective chemical tools to real-time detect and track the protein degradation. Herein, the first fluorescent and theranostic PROTACs were designed for imaging the degradation of nicotinamide phosphoribosyltransferase (NAMPT) in living cells. Compound B4 was proven to be an environmentally sensitive fluorescent PROTAC, which efficiently degraded NAMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…As illustrated in Figure 9E, both compounds ( B3 and D1 ) significantly reduced the expression levels of NAMPT in tumors, whereas the activity of compound B3 decreased after 365 nm irradiation. Previous studies have highlighted the toxicity associated with NAMPT inhibitors and NAMPT inhibitor‐based PROTACs [4d,10,15] . Throughout the administration period, noticeable weight loss was observed solely in group d mice, indicating the high toxicity of the inhibitor‐based PS‐PROTAC D1 (Figure 9F).…”
Section: Resultsmentioning
confidence: 80%
“…As illustrated in Figure 9E, both compounds ( B3 and D1 ) significantly reduced the expression levels of NAMPT in tumors, whereas the activity of compound B3 decreased after 365 nm irradiation. Previous studies have highlighted the toxicity associated with NAMPT inhibitors and NAMPT inhibitor‐based PROTACs [4d,10,15] . Throughout the administration period, noticeable weight loss was observed solely in group d mice, indicating the high toxicity of the inhibitor‐based PS‐PROTAC D1 (Figure 9F).…”
Section: Resultsmentioning
confidence: 80%
“…Previously, we designed a series of 3-pyridine-based NAMPT inhibitors and degraders. NAMPT activator 2 was featured as a 4-substituted pyridine group, a urea linker, and a hydrophobic tail group. The docking model of compound 2 with NAMPT revealed that its 4-pyridine ring formed π–π interactions with Tyr18 and Phe193.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, various natural and synthetic antiaging agents have been tested in clinical trials, such as quercetin, rapamycin, metformin, and NAD + enhancers. , Among them, NAD + enhancers have emerged as a potential therapeutic approach for improving age-related diseases and extending the lifespan . Continuing our efforts in the discovery of small molecule modulators of NAD + homeostasis, herein, we designed a series of new NAMPT activators and investigated their therapeutic effects in age-related diseases. Particularly, compound C8 effectively activated NAMPT and enhanced intracellular NAD + levels.…”
Section: Introductionmentioning
confidence: 99%
“…cIAP1, cIAP2, and X‐chromosome‐linked IAP (XIAP) belong to the family of antiapoptotic proteins that play a critical role in the control of apoptotic machinery 354–361 . The widespread use of IAPs as an E3 ligase in TPD has drawn much attention from scientists in both academia and industry 362–368 .…”
Section: Iap Ligands and Their Utilizations In Protacsmentioning
confidence: 99%